Merger and Acquisition and Firm Performance: An Analysis of Proton-Geely - Gnomblerou, Edna (Advances in Social Sciences Research Journal, 2020)
This study draws attention to a merger and acquisition case that involves Geely and Proton respectively, Chinese and Malaysian firms. The article mainly focuses on the financial performance of Geely before and after the acquisition. To achieve this, the paper adopted a qualitative research method by using archival data sources to analyze the single case of the acquisition of Proton by Geely. The sampling area is Asia being China and Malaysia describing a cross-border transaction in emerging markets. The paper performed ratio analysis to investigate the different indicators of Geely’s financial performance before and after the acquisition. After documenting and analyzing this case, the paper argues that Geely performed well before and after the acquisition. The analysis can serve as evidence of a better financial performance of Chinese firms after cross-national M&A transactions. As a qualitative research, this article benefits not only from the bibliometric analysis done through past research and official reports related to the case but also from the quality and validity required for a case study analysis. This study is an original attempt at presenting the case study of Geely’s acquisition of Proton from the lens of the acquiring firm’s performance before and after the acquisition. However, due to the limited information provided by financial ratios, the findings of the paper are not exhaustive.